(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2002)
Development is a central idea in modern culture. Yet, it has a number of ideologically diverse meanings that will be rewritten and redefined in different social science theories during this century. This article tries to show how in Argentina, a society that is not completely “A modern” or A developed”, specific local characteristics shaped the rewriting and interpretations of development at two points in the twentieth century. Giddens’ double hermeneutic theory (1984) is the central conceptual tool for the analysis.